CLINICAL AND EPIDEMIOLOGICAL ASPECTS OF ECHINOCOCCOSIS IN CHILDREN IN THE ASTRAKHAN REGION - R. S. Arakelyan; Kh. M. Galimzyanov; A. A. Zhidovinov; S. F. Karpenko; G. L. Shendo; K. G. Gasanov; Ya. O. Sokolova; N. A. Alyokhina (LLC "Diagnostics and Vaccines", 2017)
Purpose of the study: Analyze the epidemiological situation of echinococcosis in children in the Astrakhan region. In the Astrakhan region from 2001 to 2016. Registered 141 cases of echinococcosis in humans, incl. In children - 22 cases (15,6%). Among all the sick children, echinococcosis was more often reported in school-age persons - 90,9%. From the preschool age group, echinococcosis was recorded in two (9,1%) unorganized children aged 5 and 6 years. The main complaints in the majority of invasive children were pain and a feeling of heaviness in the right hypochondrium - 40,9%, periodically arising cramping pain in the area of localization of the parasite - 31,8%. In rare cases, complaints of weakness and a feeling of bursting at the site of echinococcal cyst localization were noted - 4,5% each. A part of patients - 18,2% of the complaints were absent. When diagnosing, both laboratory and instrumental diagnostic methods were used. In most cases - 90,9%, the diagnosis of echinococcosis was confirmed by the enzyme immunoassay (ELISA method). Thus, recently in the territory of the Astrakhan region there has been an increase in the number of cases of human infection with echinococcus, incl. аnd children of school age. The parasite is located, as a rule, in the liver and lung. The disease was susceptible to those who had a history of permanent contact with non-undelminthic dogs. In the diagnosis of echinococcosis, the main role is played by the complex methods of ELISA, CT, ultrasound, x-ray and histological methods.